Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila) - Wood, Thomas James; Cross, Ian; Baldock, David W. (Zootaxa, 2020)
Portugal is home to a rich but understudied bee fauna that was recently comprehensively documented for the first time. As part of ongoing work to improve the knowledge of Portuguese bees, efforts have been made to survey poorly recorded parts of the country and to continue to review existing material in museum collections. These efforts have resulted in 28 species newly discovered in Portugal, as well as eight species added from the literature and two taxa recently raised to full species status. Three additional species, Andrena (Lepidandrena) baetica spec. nov., Andrena (Micrandrena) omnilaevis spec. nov., and Andrena (Notandrena) foeniculae spec. nov. are described from material collected in southern Iberia, north-western Iberia, and southern Iberia, respectively. Andrena omnilaevis spec. nov. is the new name for north-western Iberian material previously identified as Andrena (Micrandrena) semilaevis Pérez. The male of Stelis hispanica Dusmet, previously only known from the holotype female, was also found and is described here. The taxon Andrena (Melandrena) limata mixtura Warncke has been various treated as a subspecies of A. limata Smith or A. nitida Müller. Examination of the holotype from Portugal shows that it actually belongs in its original combination Andrena limata comb. nov., and that true A. nitida is not present in Portugal. Seven additional species have been removed from the total due to misidentification or uncertainty. We also present discussion on the status of species complexes present in Portugal, and review species doubtfully recorded from the country. Altogether, this work increases the number of bee species recorded from mainland Portugal from 680 to 712, and to 722 for the country as a whole when including the faunas of the Madeira and Azores archipelagos.